Spatial dynamics and ecological restoration strategies for coastal vulnerability in Jiangsu Province, China: a multi-factorial assessment - Hou, Jiashuang; Liu, Binglin; Liu, Weijiang; Yao, Nini (Frontiers in Environmental Science, 2025)
The coastal region of Jiangsu Province, a critical ecological and economic zone in eastern China, faces significant spatial vulnerability due to combined natural and anthropogenic pressures. This study employs a multi-factorial assessment framework integrating Geographic Information System (GIS) tools to analyze vulnerability across three dimensions: basic conditions, ecological environment, and human activities. Key findings reveal distinct spatial disparities in vulnerability, quantified through a vulnerability index (VI) ranging from 1 (highest vulnerability) to 5 (lowest).Statistical results indicate that 5.49% of the coastal zone is classified as high vulnerability (VI = 1) and 21.15% as relatively high (VI = 2), primarily concentrated in inland areas such as Ganyu, Lianyun, and Binhai districts. Conversely, 39.31% of the region exhibits moderate vulnerability (VI = 3), while 32.04% and 2.02% are categorized as relatively low (VI = 4) and low vulnerability (VI = 5), respectively. Notably, inland regions consistently show higher vulnerability compared to coastal areas, contradicting initial assumptions of uniform north-south gradients. Spatial analysis further demonstrates that central coastal zones (e.g., Dafeng, Dongtai) exhibit lower vulnerability due to balanced human-environment interactions, whereas northern and southern inland regions face intensified pressures from urbanization, industrialization, and land subsidence.To address these disparities, this study proposes targeted ecological restoration strategies, including: (1) infrastructure reinforcement in high-vulnerability inland areas; (2) wetland conservation and reforestation in ecologically sensitive zones; (3) sustainable land-use planning to mitigate human-induced degradation; and (4) community-based adaptive management frameworks. These recommendations aim to enhance resilience while balancing socioeconomic development and environmental protection. This research provides a data-driven foundation for policymakers to prioritize interventions in Jiangsu’s coastal zone and offers a replicable methodology for vulnerability assessments in other deltaic regions.